2012
DOI: 10.1002/xrs.2432
|View full text |Cite
|
Sign up to set email alerts
|

Combined XRF‐SEM analysis of varnished pottery: the case of Syracuse and Adrano (Sicily) archaelogical finds

Abstract: Micro-destructive and non-destructive X-Ray fluorescence techniques and scanning electron microscopy coupled with energydispersive spectrometry have been applied for the analysis of ten samples of Hellenistic black-varnished pottery, coming from archaeological excavations in Syracuse and Adrano (South Italy, Sicily). Micro-morphological and compositional investigations, together with statistical data processing, have shown several differences among the varnishes of the specimen found in the two sites. In parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Recently, mapping analysis of clayware texture using scanning electron microscopy–energy dispersive X‐ray (SEM‐EDX) microscopy was reported in pottery analysis, producing high magnification images of the ceramic microstructure for mineralogical analysis. However, these techniques are also destructive as they require thin samples, making it unsuitable for direct measurement of potsherd surface. Portable XRF enables nondestructive chemical analysis and is a useful instrument for on‐site field research of archeological material, but this method has problems arising from atmospheric conditions and manual measurement that negatively affect quantitativity and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, mapping analysis of clayware texture using scanning electron microscopy–energy dispersive X‐ray (SEM‐EDX) microscopy was reported in pottery analysis, producing high magnification images of the ceramic microstructure for mineralogical analysis. However, these techniques are also destructive as they require thin samples, making it unsuitable for direct measurement of potsherd surface. Portable XRF enables nondestructive chemical analysis and is a useful instrument for on‐site field research of archeological material, but this method has problems arising from atmospheric conditions and manual measurement that negatively affect quantitativity and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopy, however, does not have equal sensitivity to all the mineralogical phases that might be present in ceramics. 7,18,[28][29][30][31] In particular, although numerous diffraction studies 7,[32][33][34][35] have reported the presence of hercynite in ceramics, the detection of pure hercynite with Raman spectroscopy has never been reported in the characterization of ancient pottery. The Raman spectrum of hercynite included in the RUFF project database 36 is the only published spectrum found.…”
Section: Introductionmentioning
confidence: 99%